Effect of Mindfulness-Based Therapy with Control Drug on Cognitive Distortions of Addicted Adolescents in Isfahan - Mohsen Saeid Manesh (Journal of Global Pharma Technology, 2017)
The purpose of this study was to investigate the effectiveness of mindfulness-based therapy on cognitive disorders in addicted adolescents in Isfahan city. The target population of all addicted teenagers is leaving the city of Isfahan in 1396. Sampling method was available from available centers in Isfahan province to the center of addiction treatment of rubbish in Isfahan province. After random sampling, 30 adolescent addicts who had entry criteria were randomly assigned into two experimental and control groups. After performing a pretest in two groups, the experimental group received cognitive therapy based on mind-awareness during 8 sessions of 90 minutes (once a week). During this period, the control group was on the waiting list. Then, both groups were measured in post-test and follow up. For information gathering, Abdollahzadeh and Salar Cognitive Distortion Questionnaire (2010), Tangji Self-Control Questionnaire-Form 36 (2004) was used. Data were analyzed using repeated measures ANOVA. The results of this study showed that Mindfulness-based therapy was effective on cognitive distortions and this effect continued throughout the follow-up period of one month. Based on the results of this study, Mindfulness-based therapy was effective in cognitive disturbances of addicted adolescents (p <0.05).Keywords: Mindfulness, Cognitive distortions, Self-control.